On Aesthetics and Stylistics: Contemporary Problems in Translation of Children’s Literature - Cyzio, Marta (Literatura Ludowa. Journal of Folklore and Popular Culture, 2019)
Review: Między manipulacją a autonomicznością este-tyczną – przekład literatury dla dzieci., red. E. Pieciul-Karmińska, B. Sommerfeld, A. Fi-miak-Chwiłkowska, Wydawnictwo Naukowe UAM, Poznań 2017, ss. 122.